Tracking Early Systolic Motion for Assessing Acute Response to Cardiac Resynchronization Therapy in Real Time - Villegas-Martinez, Manuel; Krogh, Magnus Reinsfelt; Andersen, Øyvind S.; Sletten, Ole Jakob; Wajdan, Ali; Odland, Hans Henrik; Elle, Ole Jakob; Remme, Espen W. (Frontiers in Physiology, 2022)
An abnormal systolic motion is frequently observed in patients with left bundle branch block (LBBB), and it has been proposed as a predictor of response to cardiac resynchronization therapy (CRT). Our goal was to investigate if this motion can be monitored with miniaturized sensors feasible for clinical use to identify response to CRT in real time. Motion sensors were attached to the septum and the left ventricular (LV) lateral wall of twenty-eight anesthetized dogs. Recordings were performed during baseline, after induction of LBBB, and during biventricular pacing. The abnormal contraction pattern in LBBB was quantified by the septal flash index (SFI) equal to the early systolic shortening of the LV septal-to-lateral wall diameter divided by the maximum shortening achieved during ejection. In baseline, with normal electrical activation, there was limited early-systolic shortening and SFI was low (9 ± 8 %). After induction of LBBB, this shortening and the SFI significantly increased (88 ± 34 %, p < 0.001). Subsequently, CRT reduced it approximately back to baseline values (13 ± 13 %, p < 0.001 vs. baseline). Furthermore, changes in SFI reflected changes in LV function (r2 = 0.76 vs. changes in stroke work). The study showed the feasibility of using miniaturized sensors for continuous monitoring of the abnormal systolic motion of the LV in LBBB and how such sensors can be used to assess response to pacing in real time to guide CRT implantation.